Impact of Grade Level on Environmental Attitudes among Students: An analysis of multiple age group - Mathura, U.; Piratheeban, K. (Open University of Sri Lanka, 2023)
A healthy and productive environment is considered the key to a sustainable human life. In order to provide adequate education on environment, environmental education is being introduced and followed in the curriculum of many countries. The Sri Lankan curriculum also has environmental education not as a separate subject but as a coordinated subject with Science and other subjects. This study was designed as a survey study under the quantitative approach to explore the impact of grade level on the environmental attitudes of students. Out of a total population of 1078 students, 285 students were selected as a sample through a stratified random sampling technique for this study. The questionnaire consisted of fifteen Likert-type questions on attitudes towards eco-friendly behaviors that were adapted from the questionnaire prepared by and modified as per the Sri Lankan context. Reliability was determined by the Cronbach Alpha test (0.749). Descriptive statistical techniques and inferential techniques such as the One-way ANOVA test and Post-Hoc LSD test were used for the analysis of collected data. Based on the significant value, no significant differences were observed for the following variables between the grades of secondary level students (P>0.05): Reading environmental-related news and articles while reading newspaper, switching off the television when no one is watching, preferring to walk to nearby places rather than going in a motorbike or other vehicles, not liking to drink anything in one-day cup at any ceremony, buying soft drinks in glass bottles or cans rather than plastic bottles, using one-side used papers for studies or Math practice, carrying re-usable shopping bags while going shopping and throwing wrapping papers and cover papers of food items in dustbins based on biodegradable and non-biodegradable varieties. However, significant differences were observed of the other seven environmental attitudes of the secondary level students and some of the grades (P<0.05). Though environmental concepts are in the curriculum from Grade Six to Eleven with the hope of involving students as partners of the environment, some grades did not show significant differences. Therefore, an emphasis on environmental concepts in the existing curriculum should be given to build positive environmental attitudes among school students in their respective grades.
Keywords: Environment; Environmental attitude; Secondary level students; Environmental behavior; Science-curriculum